Elucidating the isorhamnetin-3-O-glucoside-iNOS interaction via molecular dynamics and Hirshfeld surface analyses - Oussama Khibech; Haytham Bouammali; Yousra Hammouti; Mohamed Bouhrim; Mohammed Merzouki; Said Abadi; Mohammed Al-zharani; Fahd A. Nasr; Ashraf Ahmed Qurtam; Boufelja Bouammalli; Allal Challioui (PLoS ONE, 2025)
Inducible nitric oxide synthase (iNOS) remains a demanding metallo-enzyme target because the catalytic heme shapes both geometry and electrostatics at the binding site. We evaluated the dietary flavonol glycoside isorhamnetin-3-O-glucoside (I3OG) against mouse (3E6T) and human (3E7G) iNOS oxygenase domains using a heme-aware, auditably validated docking workflow. we centered the docking grids at the crystallographic Fe position and validated the protocol by re-docking the native co-crystallized inhibitors (3E6T: AR-C118901/1A2; 3E7G: AR-C95791/AT2), reproducing the crystal poses with heavy-atom RMSD = 1.093 Å and 0.327 Å, respectively (≤ 2.0 Å criterion). Explicit-solvent 100-ns MD confirmed stable complexes for both systems; 3E6T showed tighter ligand RMSD, lower pocket Cα-RMSF, and a more persistent H-bond network. MM/GBSA over equilibrated frames (60−100 ns) yielded ΔG_bind ≈ −44.9 ± 3.9 kcal·mol −1 (3E6T) vs −36.1 ± 3.7 kcal·mol −1 (3E7G), with per-residue hot spots matching docking contacts. Principal-component free-energy maps indicated more focused minima for 3E6T and a broader low-energy valley for 3E7G, consistent with the MD metrics. we performed an apo-form heme-cavity test (heme removed, grid kept at Fe; proximal Cys re-protonated) to probe pocket occupancy/flexibility without claiming a catalytic model. Collectively, the heme-centred, co-crystal-validated protocol plus the apo-cavity readout support I3OG as a plausible scaffold for iNOS engagement and provide a transparent template for future metallo-enzyme docking studies.